2020
DOI: 10.1016/j.trip.2020.100193
|View full text |Cite
|
Sign up to set email alerts
|

Activating inclusive growth in railway SMEs by workplace innovation

Abstract: The digital revolution is happening, transforming the way we move and produce. Success in the digital revolution means that the rail industries need to use the best available technologies focusing on people. The managerial and organizational practices adopted by railway entities have considerable significance for Railway's ability to succeed in global competition. One of the challenges for railway entities is to deliver innovative products, offering quickness and flexibility to respond to changing demands from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…The commitment and motivation of human resources with respect to innovation behaviours play an important role in the relationship between OI and firm performance. 30 Such a relationship is analysed by Zhang et al 48 Their findings show that in most cases, a high level of employee education leads to an increase in the positive effect of OI. However, the authors reveal that in production-oriented companies, this does not always happen.…”
Section: Overview Of the Analysed Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The commitment and motivation of human resources with respect to innovation behaviours play an important role in the relationship between OI and firm performance. 30 Such a relationship is analysed by Zhang et al 48 Their findings show that in most cases, a high level of employee education leads to an increase in the positive effect of OI. However, the authors reveal that in production-oriented companies, this does not always happen.…”
Section: Overview Of the Analysed Trendsmentioning
confidence: 99%
“…Despite a number of existing studies addressing similar arguments, 30 –33 the aim of this paper is as follows: (i) to investigate how the OI paradigm affects firm performance, both generally and by means of a comprehensive and systematic review of such studies providing the most unique insights into the topic; (ii) to identify the main thematic areas; and (iii) provide suggestions for future research avenues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the organizational level, the results revealed that organizational factors have different impacts on innovation climate. Employee-driven creativity influences the daily evolution of WI practices and gradual improvements, most railway organizations do not use their autonomy to improve WI practices [16]. These findings depart from the WI existing studies that suggest job autonomy can be relevant to guide one's behavioral intentions and has influence positively the company performance [16,18].…”
Section: Discussionmentioning
confidence: 96%
“…The literature confirms the digital transformation is influenced by the culture of innovation, the high levels of employee commitment and the capacity for organizational and individual transformation. Digital transformation is the key to business competitiveness in a changing and increasingly demanding market [16]. However, a culture that encourages innovation and creativity is needed to succeed in the railway technological transformation.…”
Section: Discussionmentioning
confidence: 99%